Evaluation of human auditory system immunity under central auditory processing disorders - Boboshko, M. Yu; Berdnikova, I. P.; Maltseva, N. V.; Kaplun, D. I.; Gulvanskiy, V. V.; Voznesenskiy, A. S. (2017 XX IEEE International Conference on Soft Computing and Measurements (SCM), 2017)
The evaluation of central auditory pathways functioning was performed with the use of psychoacoustic tests, which characterize binaural interaction in the human auditory system, as well as the ability to detect sound stimulus in background tone. 20 patients with chronic bilateral symmetric sensorineural hearing loss from 31 to 80 years old and 10 patients from 20 to 25 years old with normal hearing were examined. Studies on the detection of a sound signal in background tone allowed us to offer a new test to assess central auditory pathways - a measurement of the useful signal threshold shift in conditions of simultaneous presentation of tonal interference. Significantly greater signal threshold shifts in simultaneous masking were revealed in patients with sensorineural hearing loss accompanying by impaired binaural interaction in comparison with patients with peripheral hearing loss and normal hearing.